Improving Hospital Discharge Time. Issue 12 (March 2015) - El-Eid, Ghada R.; Kaddoum, Roland; Tamim, Hani; Hitti, Eveline A.; Harris., Kevin
<x xml:space="preserve">Abstract</x> Abstract Delays in discharging patients can impact hospital and emergency department (ED) throughput. The discharge process is complex and involves setting specific challenges that limit generalizability of solutions. The aim of this study was to assess the effectiveness of using Six Sigma methods to improve the patient discharge process. This is a quantitative pre and post-intervention study. Three hundred and eighty-six bed tertiary care hospital. A series of Six Sigma driven interventions over a 10-month period. The primary outcome was discharge time (time from discharge order to patient leaving the room). Secondary outcome measures included percent of patients whose discharge order was written before noon, percent of patients leaving the room by noon, hospital length of stay (LOS), and LOS of admitted ED patients. Discharge time decreased by 22.7% from 2.2 hours during the preintervention period to 1.7 hours post-intervention (P < 0.001). A greater proportion of patients left their room before noon in the postintervention period (P < 0.001), though there was no statistical difference in before noon discharge. Hospital LOS dropped from 3.4 to 3.1 days postintervention (P < 0.001). ED mean LOS of patients admitted to the hospital was significantly lower in the postintervention period (6.9 ± 7.8 vs 5.9 ± 7.7 hours; P < 0.001). Six Sigma methodology can be an effective change management tool to improve discharge time. The focus of institutions aspiring to tackle delays in the discharge process should be on adopting the core principles of Six Sigma rather than specific interventions that may be institution-specific.